1996
DOI: 10.1073/pnas.93.20.11068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the endothelial cell binding site for factor IX.

Abstract: We previously demonstrated that the primary region of factor IX and IXa responsible for saturable specific binding to bovine aortic endothelial cells resides in residues 3-11 at the amino terminus of factor IX. We also demonstrated that mutations of lysine to alanine at residue 5, factor IX K5A, or valine to lysine at residue 10, factor IX V10K, resulted in a molecule unable to bind to endothelial cells.Moreover, a mutation with lysine to arginine at residue 5, factor IX K5R, resulted in a factor IX molecule w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 29 publications
1
103
1
Order By: Relevance
“…21,22 While these results support the safe transduction of the target muscle by rAAV vectors leading to human factor IX expression, we cannot rule out from our studies that expressed factor IX may be bound locally, and thus sequestered from efficient delivery into the circulation. 23 It is interesting to note that the level of expression of factor IX observed in vitro increased gradually over 1 week after infection, achieving levels comparable to those previously reported in hemophilic dog fibroblasts following retroviral or adenovirus-polylysine-DNA factor IX gene delivery. 4,24 This increase with time is not unexpected, as both in vivo and in vitro experiments suggest AAV transduction increases gradually, reaching a plateau in the first weeks after infection 3,8 (also, Snyder and Muzyczka personal communication).…”
Section: Discussionsupporting
confidence: 79%
“…21,22 While these results support the safe transduction of the target muscle by rAAV vectors leading to human factor IX expression, we cannot rule out from our studies that expressed factor IX may be bound locally, and thus sequestered from efficient delivery into the circulation. 23 It is interesting to note that the level of expression of factor IX observed in vitro increased gradually over 1 week after infection, achieving levels comparable to those previously reported in hemophilic dog fibroblasts following retroviral or adenovirus-polylysine-DNA factor IX gene delivery. 4,24 This increase with time is not unexpected, as both in vivo and in vitro experiments suggest AAV transduction increases gradually, reaching a plateau in the first weeks after infection 3,8 (also, Snyder and Muzyczka personal communication).…”
Section: Discussionsupporting
confidence: 79%
“…Amino acids 3-11 in the FIX Gla domain are critical for high affinity binding of the protein to aortic endothelial cells (57). It appears that this interaction is caused by binding of FIX to collagen IV and not phospholipid in the cell membrane (58). Using scanning force microscopy, Wolberg and colleagues (59) demonstrated that FIX binds specifically to collagen IV in the later molecule collagenous domain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unique protein-protein interactions sometimes involve the Gla domain. For example, factor IXa, factor VIIa, and protein C have been shown to bind specifically to collagen IV (20), tissue factor (21), and endothelial protein C receptor (22), respec-tively, through the Gla domain.…”
mentioning
confidence: 99%